Neuroergonomics
XXIV, 248 p.
Keywords: This book covers the foundations and successes of Neuroergonomics, combining neuroscience and ergonomics to enhance efficiency and safety. An overview of the essential areas within the field is given including chapters on brain networks, perception, attention, and performance.